Long working hours and risk of 50 health conditions and mortality outcomes: a multicohort study in four European countries - Ervasti Jenni; Pentti Jaana; Nyberg Solja T; Shipley Martin J; Leineweber Constanze; Sørensen Jeppe K; Alfredsson Lars; Bjorner Jakob B; Borritz Marianne; Burr Hermann; Knutsson Anders; Madsen Ida EH; et al. (ELSEVIER, 2022)
Background
Studies on the association between long working hours and health have captured only a narrow range of outcomes (mainly cardiometabolic diseases and depression) and no outcome-wide studies on this topic are available. To achieve wider scope of potential harm, we examined long working hours as a risk factor for a wide range of disease and mortality endpoints.
Methods
The data of this multicohort study were from two population cohorts from Finland (primary analysis, n=59 599) and nine cohorts (replication analysis, n=44 262) from Sweden, Denmark, and the UK, all part of the Individual-participant Meta-analysis in Working Populations (IPD-Work) consortium. Baseline assessed long working hours (>55 hours per week) were compared to standard working hours (35-40 h). Outcome measures with follow-up until age 65 years were 46 diseases that required hospital treatment or continuous pharmacotherapy, all-cause, and three cause-specific mortality endpoints, ascertained via linkage to national health and mortality registers.
Findings
2747 (4.6%) participants in the primary cohorts and 3027 (6.8%) in the replication cohorts worked long hours. After adjustment for age, sex, and socioeconomic status, working long hours was associated with increased risk of cardiovascular death (hazard ratio 1.68; 95% confidence interval 1.08-2.61 in primary analysis and 1.52; 0.90-2.58 in replication analysis), infections (1.37; 1.13-1.67 and 1.45; 1.13-1.87), diabetes (1.18; 1.01-1.38 and 1.41; 0.98-2.02), injuries (1.22; 1.00-1.50 and 1.18; 0.98-1.18) and musculoskeletal disorders (1.15; 1.06-1.26 and 1.13; 1.00-1.27). Working long hours was not associated with all-cause mortality.
Interpretation
Follow-up of 50 health outcomes in four European countries suggests that working long hours is associated with an elevated risk of early cardiovascular death and hospital-treated infections before age 65. Associations, albeit weak, were also observed with diabetes, musculoskeletal disorders and injuries. In these data working long hours was not related to elevated overall mortality.